The nexus of self-regulation with academic performance of high school students - Bibi, Paghunda; Ahmad, Nizar; Ullah, Farhat (The Journal of Humanities & Social Sciences, 2022)
In the current situation in Pakistan, teachers and parents are pressing students to get good grades. Students are pushed for hard work, out-of-school tuition and long hours of study. Several factors influence students’ academic performance. Self-regulation is one of them. However, limited studies account for students’ self-regulatory abilities at school and their academic performance in Pakistan. To fill this gap, this study explores the nexus of self-regulation with the academic performance of high school students. For this purpose, a cross-sectional survey was conducted at four selected schools in District Charsadda, Khyber Pakhtunkhwa, Pakistan. Data were collected from 200 hundred high school students, both male and female. The study measured the association of five elements of self-regulation, namely goal setting, goal attainment, mindfulness, pro-activeness and adjustment, with students’ academic performance. The results revealed a highly significant association of various aspects of self-regulation, such as goal setting, goal attainment, mindfulness and pro-activeness with students’ academic performance. However, adjustment was insignificantly associated with students’ academic performance. The study suggests teachers and parents should help and support students adjust their academic plans when students find it difficult to achieve their academic goals.